Padrão sazonal da qualidade do solo, água, regimes térmicos e desempenho de culturas para biocombustíveis sob diferentes práticas de manejo - Awe, Gabriel Oladele (2014)
The intensification of biofuel production causes negative impacts on soil quality, thus the soil requires adequate assessment to ascertain its quality status, however site-specific nature of results in literature requires independent soil property measurement and assessment depending on specific agroecosystem and management goals. Therefore, the main objective of this study was to investigate seasonal pattern of soil quality, soil water and thermal regimes and performance of sugarcane and tung crops at the experimental station of Soils Department, Federal University of Santa Maria, Santa Maria, RS, Brazil. The sugarcane experiment (three seasons) was established in 2010 under no-tillage; no-tillage + compaction; conventional tillage and chiseling treatments in a randomized complete block design with three replications. In years 2011 and 2012, there was no soil disturbance; however residue mulching was imposed, giving split-plot design. The tung-based cropping system (two seasons, 2012-2014) was a randomized complete block design experiment with four replications. The treatments were: tung-crambe-sunflower/soybean + inorganic fertilizer; tung-crambe-sunflower/soybean + organic manure; tung-oats-peanut; and sole tung (control). Crambe and oats were planted in winter while sunflower (1st year)/soybean (2nd year) and peanut were planted in summer. Disturbed and undisturbed (using cores of known volume) soil samples were collected from soil layers 0-10, 10-20, 20-40 and 40-60 cm in sugarcane, and 0-10, 10-20, 20-40, 40-60 and 60-80 cm in tung for the laboratory determination of soil quality indicators. There was field monitoring of soil water retention, matric potential and soil temperature and agronomic parameters measured include sugarcane yield and tung plant height. Minimum data set for soil quality assessment was made using principal component analysis and soil quality index was obtained using weighted additive method. The temporal patterns of soil water storage and temperature were evaluated using algorithms for time series data. Except for Ma in 0-10 cm layer of tillage plots, both tillage and residue mulching did not significantly affect (p<0.05) the soil quality indicators, overall soil quality, water retention and sugarcane yield. The degree of compaction was not enough to limit sugarcane growth. Residue retention significantly influenced temporal processes of soil temperature and state-time analysis was better than classical regression of time series analysis of soil water storage and temperature. Cropping system did not significantly influence (p<0.05) soil quality indicators, overall SQI and tung plant height, but significant influenced soil water retention. For the two experiments, there was no discernible trend in the seasonal values of soil hydro-physical variables and crop response.